Fatty acid profile in peri-prostatic adipose tissue and prostate cancer aggressiveness in African–Caribbean and Caucasian patients. (March 2018) - Figiel, Sandy; Pinault, Michelle; Domingo, Isabelle; Guimaraes, Cyrille; Guibon, Roseline; Besson, Pierre; Tavernier, Elsa; Blanchet, Pascal; Multigner, Luc; Bruyère, Franck; Haillot, Olivier; Mathieu, Romain; et al.
Abstract: Background: Genetic and nutritional factors have been linked to the risk of aggressive prostate cancer (PCa). The fatty acid (FA) composition of peri-prostatic adipose tissue (PPAT), which reflects the past FA intake, is potentially involved in PCa progression. We analysed the FA composition of PPAT, in correlation with the ethno-geographical origin of the patients and markers of tumour aggressiveness. Methods: From a cohort of 1000 men treated for PCa by radical prostatectomy, FA composition of PPAT was analysed in 156 patients (106 Caucasians and 50 African–Caribbeans), 78 with an indolent tumour (ISUP group 1 + pT2 + PSA <10 ng/mL) and 78 with an aggressive tumour (ISUP group 4–5 + pT3). The effect of FA extracted from PPAT on in-vitro migration of PCa cells DU145 was studied in 72 patients, 36 Caucasians, and 36 African–Caribbeans. Results: FA composition differed according to the ethno-geographical origin. Linoleic acid, an essential n-6 FA, was 2-fold higher in African–Caribbeans compared with Caucasian patients, regardless of disease aggressiveness. In African–Caribbeans, the FA profile associated with PCa aggressiveness was characterised by low level of linoleic acid along with high levels of saturates. In Caucasians, a weak and negative association was observed between eicosapentaenoic acid level (an n-3 FA) and disease aggressiveness. In-vitro migration of PCa cells using PPAT from African–Caribbean patients was associated with lower content of linoleic acid. Conclusion: These results highlight an important ethno-geographical variation of PPAT, in both their FA content and association with tumour aggressiveness. Highlights: Fatty acid composition of peri-prostatic adipose tissue (PPAT) varies according to the ethno-geographical origin. Linoleic acid content is 2-fold higher in African–Caribbeans' PPAT regardless of disease aggressiveness. PCa aggressiveness is associated with low n-6 content in African–Caribbeans. PCa aggressiveness is associated with low EPA (n-3) content in Caucasians. In-vitro migration of PCa cells is associated with low linoleic acid content in PPAT.